Analisis Faktor-Faktor Penentu Peran Kelompok Tani Dalam Meningkatkan Produktivitas Padi Sawah (Oryza Sativa) Di Desa Nanjungan - Okta Indarti; Yossie Yumiati; Rika Dwi Yulihartika (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Rice farmers in Nanjungan Village, Semidang Alas Sub-District, Seluma Regency, some experience difficulties or fail to increase productivity due to limited agricultural technology, access to production facilities, and weak farmer institutions, so that many farmers depend on the role of farmer groups to meet their daily production and welfare needs. The objectives of this research are (1) to determine the level of role of farmer groups in increasing rice paddy productivity in Nanjungan Village, Semidang Alas Sub-District, Seluma Regency, (2) to determine what factors influence the role of farmer groups in increasing rice paddy productivity in Nanjungan Village, Semidang Alas Sub-District, Seluma Regency. The research method used is a quantitative method using descriptive analysis, Likert scale and multiple linear regression. The results of the research show that the role of farmer groups in increasing rice paddy productivity is on average 34.81, which means that the role of farmer groups is in the high category. Factors influencing the role of farmer groups in increasing lowland rice productivity include the function and governance of farmer groups (X1), extension support and mentoring (X3), and member participation and cooperation (X4). Meamshile, the application of technology and mnovation (X2), as well as external cooperation and market access (X5), do not influence, the role of farmer groups.